The Role of Sirtuin-1 in Immune Response and Systemic Lupus Erythematosus - Qiu, Yueqi; Zhou, Xingyu; Liu, Yu; Tan, Siqi; Li, Yaping (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is a potentially fatal multisystem inflammatory chronic disorder, the etiology and pathogenesis of which remain unclear. The loss of immune tolerance in SLE patients contributes to the production of autoantibodies that attack multiple organs and tissues, such as the skin, joints, and kidneys. Immune cells play important roles in the occurrence and progression of SLE through amplified immune responses. Sirtuin-1 (SIRT1), an NAD+-dependent histone deacetylase, has been shown to be a pivotal regulator in various physiological processes, including cell differentiation, apoptosis, metabolism, aging, and immune responses, via modulation of different signaling pathways, such as the nuclear factor κ-light-chain-enhancer of activated B cells and activator protein 1 pathways. Recent studies have provided evidence that SIRT1 could be a regulatory element in the immune system, whose altered functions are likely relevant to SLE development. This review aims to illustrate the functions of SIRT1 in different types of immune cells and the potential roles of SIRT1 in the SLE pathogenesis and its therapeutic perspectives.